1997
DOI: 10.1007/s11745-997-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short‐term diets rich in fish, red meat, or white meat on thromboxane and prostacyclin synthesis in humans

Abstract: Foods which increase tissue arachidonic acid levels have been proposed to increase thrombosis tendency, presumably through increased platelet aggregation. This study examined the effect of doubling the dietary arachidonic acid (20:4n-6) using meat- or fish-based diets on the systemic production of prostacyclin (PGI2) and thromboxane (TXA2) in 29 healthy, nonsmoking adults. There were three, 3-wk low-fat dietary periods (< 15% energy as fat) in which subjects consumed a vegetarian diet for 1 wk followed by 2 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 65 publications
1
23
0
1
Order By: Relevance
“…However, beef and lamb had a notably higher n-3 level in the lean tissue than the poultry and pork and a much lower n-6/n-3 ratio in lean and fat tissue than did the subcutaneous fat of poultry and pork (<2 compared with >9). These differences in n-3 PUFA levels in red and white meat are reflected in the serum phospholipid fatty acid of subjects consuming red and white meats (8). No long-chain n-3 PUFA were detected in the visible fat samples (<0.01% total fatty acids) and only trace amounts of long-chain n-6 PUFA.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, beef and lamb had a notably higher n-3 level in the lean tissue than the poultry and pork and a much lower n-6/n-3 ratio in lean and fat tissue than did the subcutaneous fat of poultry and pork (<2 compared with >9). These differences in n-3 PUFA levels in red and white meat are reflected in the serum phospholipid fatty acid of subjects consuming red and white meats (8). No long-chain n-3 PUFA were detected in the visible fat samples (<0.01% total fatty acids) and only trace amounts of long-chain n-6 PUFA.…”
Section: Resultsmentioning
confidence: 91%
“…Ferretti et al (6) confirmed that 1.5 g/d of AA fed to 10 healthy male volunteers for 50 d led to a significant increase in metabolites of thromboxane A 2 and prostacyclin; however, these changes were not associated with increased platelet aggregation (7). Consumption of either red or white meat leads to increased levels of AA in plasma lipids (8).…”
mentioning
confidence: 95%
“…However, the in vivo conversion of dietary ALA to EPA is not as effective in raising 20-and 22-carbon nϪ3 long-chain PUFAs in platelet and plasma lipids as is direct consumption of EPA from fish or supplementation with fish oil (22). Mann et al (23) reported that the EPA content of platelet phospholipids increased (from 0.4% to 1.9% of total fatty acids) after 2 wk of an Atlantic salmon diet (mean EPA intake: 847 mg/d) in 29 healthy adults (15 women, 14 men; mean age: 34.8 y). In the present study, the high-ALA diet, which contained 15.4 g ALA/d, increased the EPA content of platelet phospholipids only from 0.2% to 0.5%.…”
Section: Tablementioning
confidence: 99%
“…Previous short term intervention studies from this group have indicated that low fat diets enriched in AA signi®-cantly increased plasma AA levels and TXA 2 production, whereas diets containing AA and long chain (LC) n-3 PUFA or diets rich in LC n-3 PUFA do not raise TXA 2 levels (Sinclair & Mann, 1996;Mann et al, 1997). One of the dif®culties with previous studies is that they have been only conducted for short periods (2 ± 3 weeks), due to the dif®culty subjects had consuming higher amounts of meat than normal.…”
Section: Introductionmentioning
confidence: 99%